The use of remote sensing data for drought assessment and monitoring in southwest Asia - Thenkabail, Prasad S.; Gamage, M.S.D.Nilantha; Smakhtin, Vladimir U. (International Water Management Institute, 2004)
This report describes the development of the near real-time drought monitoring and reporting system for the region, which currently includes Afghanistan, Pakistan and western parts of India. The system is based on drought-related indices derived from high-resolution remote-sensing data (MODIS). The unique feature of the study is the development of regression relationships between drought-related indices obtained from MODIS and AVHRR data, which have different pixel-resolution and optical characteristics. The goal is to make the system available, via Internet, to all stakeholders in the region.